SANITATION SECTOR - Dianderas Salhuana, Augusta (2022)
The purpose of this article is to analyze the gap that exists in the drinking water and sewage service; and proposes alternatives to reduce these gaps, between the rural and urban population. Making a retrospective analysis, the study shows graphs and statistical tables where the evolution is observerd of water and sewage converage in rural and urban areas, showing a significant gap between these indicators. Conclude that, despite the fact that the government has been allocating a larger budget to the populations, it has not been posible to significantly reduce these gaps, evidencing the lack of efficiency and effectiveness of the contry’s institutions.